Knowledge, facilitators and barriers to cervical cancer screening among women in Uganda: a qualitative study. Issue 6 (11th June 2017) - Ndejjo, Rawlance; Mukama, Trasias; Kiguli, Juliet; Musoke, David
Abstract : Objectives: To explore community knowledge, facilitators and barriers to cervical cancer screening among women in rural Uganda so as to generate data to inform interventions. Design: A qualitative study using focus group discussions and key informant interviews. Setting: Discussions and interviews carried out in the community within two districts in Eastern Uganda. Participants: Ten ( 10) focus group discussions with 119 screening-eligible women aged between 25 and 49 years and 11 key informant interviews with healthcare providers and administrators. Results: Study participants' knowledge about cervical cancer causes, signs and symptoms, testing methods and prevention was poor. Many participants attributed the cause of cervical cancer to use of contraception while key informants said that some believed it was due to witchcraft. Perceptions towards cervical cancer and screening were majorly positive with many participants stating that they were at risk of getting cervical cancer. The facilitators to accessing cervical cancer screening were: experiencing signs and symptoms of cervical cancer, family history of the disease and awareness of the disease/screening service. Lack of knowledge about cervical cancer and screening, health system challenges, fear of test outcome and consequences and financial constraints were barriers to cervical cancer screening. Conclusion: Whereas perceptions towards cervical cancer and screening were positive, knowledge of study participants on cervical cancer was poor. To improve cervical cancer screening, effort should be focused on reducing identified barriers and enhancing facilitators.